Lipopolysaccharide-Deficient Acinetobacter baumannii Due to Colistin Resistance Is Killed by Neutrophil-Produced Lysozyme - Kamoshida, Go; Akaji, Takuya; Takemoto, Norihiko; Suzuki, Yusuke; Sato, Yoshinori; Kai, Daichi; Hibino, Taishi; Yamaguchi, Daiki; Kikuchi-Ueda, Takane; Nishida, Satoshi; Unno, Yuka; Tansho-Nagakawa, Shigeru; et al. (Frontiers in Microbiology, 2020)
Acinetobacter baumannii causes nosocomial infections due to its multi-drug resistance and high environmental adaptability. Colistin is a polypeptide antibacterial agent that targets lipopolysaccharide (LPS) and is currently used to control serious multidrug resistant Gram-negative bacterial infections, including those caused by A. baumannii. However, A. baumannii may acquire colistin resistance by losing their LPS. In mouse models, LPS-deficient A. baumannii have attenuated virulence. Nevertheless, the mechanism through which the pathogen is cleared by host immune cells is unknown. Here, we established colistin-resistant A. baumannii strains and analyzed possible mechanisms through which they are cleared by neutrophils. Colistin-resistant, LPS-deficient strains harbor mutations or insertion sequence (IS) in lpx genes, and introduction of intact lpx genes restored LPS-deficiency. Analysis of interactions between these strains and neutrophils revealed that compared with wild type, LPS-deficient A. baumannii only weakly stimulated neutrophils, with consequent reduced levels of reactive oxygen species (ROS) and inflammatory cytokine production. Nonetheless, neutrophils preferentially killed LPS-deficient A. baumannii compared to wild type strains. Moreover, LPS-deficient A. baumannii strains presented with increased sensitivities to antibacterial lysozyme and lactoferrin. We revealed that neutrophil-secreted lysozyme was the antimicrobial factor during clearance of LPS-deficient A. baumannii strains. These findings may inform the development of targeted therapeutics aimed to treat multi-drug resistant infections in immunocompromised patients who are unable to mount an appropriate cell-mediated immune response.